IMPLIKASI KINERJA INTERNAL PERBANKAN SYARIAH DAN GEJOLAK INDIKATOR MAKROEKONOMI TERHADAP AKSELERASI PEMBIAYAAN BANK UMUM SYARIAH DI INDONESIA - Widodo, Arif; Agustiyani, Mahmudah (EQUILIBRIUM, 2017)
This study aims to analyze the financing of Sharia Commercial Banks in Indonesia that is influenced by the internal quality of banking performance and macroeconomic situation turmoil. It was quantitative research using Data Panel method analysis tool. This study used secondary data in the form of time series and individual (cross section) data in quarterly form during the period of 2011 to 2015, obtained from the Otoritas Jasa Keuangan (OJK), the report of the dollar exchange rate against the rupiah published in daily newspaper Bisnis or Kontan, and Financial Statements published by Sharia Commercial Banks. The results of this study indicate that the third party fund as the main source of banking funds that can encourage the growth of financing, and variable exchange rate dollar / Rp have a significant positive effect on Islamic banking financing. As for the variable Capital Adequacy Ratio (CAR) and Interest Rate does not significantly affect the financing of sharia banking in Indonesia. Macroeconomic factor that can affect the financing of sharia banking is the dollar/Rp. When the dollar exchange is strengthened, demand for financing in sharia banks is also high.